PRUNE BELLY SYNDROME: A CASE REPORT - M.I. Solodkiy; K.A. Dzhuma; R.V. Zhezhera; O.J. Vylkov (Ukrainian Journal of Nephrology and Dialysis, 2014)
Prune belly syndrome (PBS) is a rare congenital anomaly almost exclusive to males defined by the triad of abdominal muscle deficiency, severe urinary tract abnormality and cryptorchidism. The syndrome has a broad spectrum of affected anatomy with different levels of severity. We report a newborn boy with PBS. Diagnosis was confirmed by karyotyping, ultrasound investigation and intraoperative findings.